2022
DOI: 10.3390/polym14204321
|View full text |Cite
|
Sign up to set email alerts
|

High Performance Composites Based on Highly Filled Glass Fiber-Reinforced Polybenzoxazine for Post Application

Abstract: Glass fiber post based on the new polymeric material, polybenzoxazine, is prepared and the effects of glass fiber contents on mechanical and thermal properties are evaluated. The mechanical response to externally applied loads of tooth restored with glass fiber-reinforced polybenzoxazine composite posts is also simulated by finite element analysis of a tridimensional model and compared with the response to that of a natural tooth. The reinforcing of glass fiber can help improve the mechanical and thermal prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…The increasing industrial demands for high-performance materials, combined with the necessity of reducing the negative environmental impact of these materials, have generated interest in both research and industrial applications. Currently, there are two main areas of research: on the one hand, materials that withstand extreme conditions [ 14 ]. On the other hand, more sustainable materials can be developed by reducing the environmental impact by providing recyclability strategies to the material [ 15 ] or the use of more sustainable feedstock.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing industrial demands for high-performance materials, combined with the necessity of reducing the negative environmental impact of these materials, have generated interest in both research and industrial applications. Currently, there are two main areas of research: on the one hand, materials that withstand extreme conditions [ 14 ]. On the other hand, more sustainable materials can be developed by reducing the environmental impact by providing recyclability strategies to the material [ 15 ] or the use of more sustainable feedstock.…”
Section: Introductionmentioning
confidence: 99%
“…The potential reinforcing fibers widely applied for composite post such as carbon fiber, polyethylene fiber, especially glass fiber etc. Mora et al (2022) have developed fiber post based on glass fiber reinforced polybenzoxazine [2a]. They suggested that the fiber content in composite materials affected on the mechanical properties of their developed posts.…”
Section: Introductionmentioning
confidence: 99%
“…Fiber-reinforced polymer composites, polymer matrix reinforced with fibers such as glass, carbon, aramid, or natural fibers of plant origin, are commonly used in the construction, marine, automotive, and aerospace industries (Bhardwaj et al 2021;Birniwa et al 2023;Shadhin et al 2021;Zhang et al 2022;Zulkifli et al 2016). In recent years, the evolution of fiber-reinforced polymer composite posts (non-metallic posts) or fiber posts as an alternative to metal and ceramic posts to reinforce tooth treated with endodontics has been investigated (Genovese et al 2005;Mora et al 2022;Pegoretti et al 2002) due to the increasing demand for tooth-colored posts, the low biocompatibility and corrosion risk of cast metal posts, and the negative aesthetic impact. Among of fiber posts, conventional epoxies acted as a polymer matrix were the most widely used polymer bases.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-linked epoxy also has a problem, i.e., low thermal stability and moderate thermal expansion (Kurihara et al 2012). In consequently, the recent studies are found the resins or polymers such as polybenzoxazine (a novel type of phenolic resin) and polyimide to substitute the conventional polymers for fiber posts (Elsubeihi et al 2020;Mora et al 2022). Additionally, the use of highly toxic hardeners for epoxies and the perception of hazardous industrial processes needs to be overcome.…”
Section: Introductionmentioning
confidence: 99%